(untitled) (Northern International Medical College Journal, 2015)
Background: During the last two decades with the application of advanced technological supports have improved the survival rate of preterm very low birth weight (PT VLBW) infants. At the same time anemia of prematurity (AOP) one of the most frequent complications of these patients also has been increased in the neonatal units. Packed red blood cell (PRBC) transfusions are the mainstay of treatment of AOP. The frequency of blood transfusion is directly related to the exposure of the tiny preterm infants to various risks of transfusion. Objectives : To evaluate whether recombinant human erythropoietin (rHuEPO) therapy reduces the need of transfusions in AOP. Methods : A randomized controlled trial study was carried out at Neonatal Unit and Intensive Care Unit (ICU) of Dhaka Shishu (children) Hospital, Dhaka, Bangladesh with 60 PTVLBW neonates. Among them 30 in group I (rHuEPO group) and 30 in group II (control) were assigned. Therapy with rHuEPO (200 IU / kg / dose) thrice weekly was initiated on day 7 of life to group I for 2 weeks. From day 14 or after that as soon as enteral feeding was initiated oral iron and folic acid were received by both groups. Hematological assessment (haemoglobin, haematocrit level and reticulocyte count) were done at 6 and 10 weeks of life. Results : At the time of enrollment in the study PTLBW babies of both groups were almost similar in gestetional age, birth weight, hemoglobin, hematocrit values and reticulocyte count (p>0.05). During the 10 weeks observation period, hematological values were increased and the number of blood transfusions as well as the number of infants who received any transfusion were reduced in rHuEPO group compared to control group (p<0.01). No adverse effect of erythropoietin were found. Conclusion : The combination of rHuEPO and Iron, folic acid therapy significantly reduces the number of blood transfusion as well as the percentage of infants who received any transfusion in AOP. Northern International Medical College Journal Vol.6(2) 2015: 53-56